Concentric quadriceps and hamstrings isokinetic strength in volleyball and soccer players - Magalhaes, J.; Oliveira, J.; Ascensao, A.; Soares, J. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Muscular strength is one of the most important components of sport, both for high performance and for injury prevention. One of the most used methods to assess strength muscle balance between dominant (D)/non-dominant (ND) and antagonist/agonist is isokinetic testing. The main purpose of the present study was to describe and to compare isokinetic strength profiles (peak torque, bilateral strength differences between D/ND leg (BD) and hamstrings/quadriceps (H/Q) ratio) in athletes of different sports and positional roles. METHODS: Twenty-eight elite volleyball players and 47 pro soccer players (goalkeepers, n = 5; full-backs, n = 7; defenders, n = 10; midfielders, n = 15; forwards, n = 10) were evaluated using an isokinetic dynamometer (Biodex-System 2). Maximal gravity corrected concentric peak torque of knee extensor and flexor muscles were measured at angular velocities of 360 degrees x s(-1) (6.28 rad x s(-1)) and 90 degrees x s(-1) (1.57 rad x s(-1)). RESULTS: No significant BD were found between soccer and volleyball players with exception of hamstrings at 90 degrees x s(-1) (soccer: 10.6 +/- 8.0% vs volleyball: 6.9 +/- 5.5%). The H/Q ratio was significantly lower in volleyball players at 90 degrees x s(-1) (D: soccer 57.4 +/- 6.7% vs volleyball 50.4 +/- 7.2%; ND: soccer: 56.1 +/- 8.2% vs volleyball: 50.5 +/- 6.4%). No significant differences were found for BD and H/Q ratio in soccer players of different positional roles. CONCLUSION: In general, soccer and volleyball players do not seem to be different concerning BD although a significant difference was observed in hamstrings at 90 degrees x s(-1). Moreover, our data suggest that specific demands of these sports and the different positional roles in soccer did not induce bilateral leg imbalances. However, sport demands seem to influence isokinetic concentric H/Q ratio.